2021
DOI: 10.1039/d1tb02170b
|View full text |Cite|
|
Sign up to set email alerts
|

Microenvironment-responsive multifunctional hydrogels with spatiotemporal sequential release of tailored recombinant human collagen type III for the rapid repair of infected chronic diabetic wounds

Abstract: A brand-new tailored hCol III-based microenvironment-responsive hydrogel could effectively accelerate the repair and regeneration of chronic diabetic wounds by a programmed controlled release of therapeutic substance approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Such a hydrogel was excellent for satisfying the substance needs of various stages of wound healing. [ 141 ] In addition to collagen, proline, a procollagen component was also implanted into a nanofiber network to stimulate fibroblast proliferation. [ 109b ]…”
Section: Nanomedical Strategies For Dfu Treatmentmentioning
confidence: 99%
“…Such a hydrogel was excellent for satisfying the substance needs of various stages of wound healing. [ 141 ] In addition to collagen, proline, a procollagen component was also implanted into a nanofiber network to stimulate fibroblast proliferation. [ 109b ]…”
Section: Nanomedical Strategies For Dfu Treatmentmentioning
confidence: 99%
“…To meet the multi-level response of smart wound dressings, Wang's group prepared a series of pH/ROS responsive hydrogel dressings through a feasible low-cost and simple synthetic procedure. [143][144][145][146] For example, as shown in Fig. 10, they pre-…”
Section: Dual/multiple Stimulus Responsive Wound Dressingsmentioning
confidence: 99%
“…To meet the multi-level response of smart wound dressings, Wang's group prepared a series of pH/ROS responsive hydrogel dressings through a feasible low-cost and simple synthetic procedure. 143–146 For example, as shown in Fig. 10, they prepared a smart hydrogel dressing using phenylboronic acid-grafted gelatin and PVA, and the hydrogel was further loaded with vancomycin-conjugated silver nanoclusters (VAN-AgNCs) and nimesulide (NIM) encapsulated by a pH-sensitive micelle.…”
Section: Smart Responsive Multifunctional Wound Dressingsmentioning
confidence: 99%
“…Inspired by the excellent effect of the recombinant humanized collagen type III (rhCol III) in promoting endothelial cell proliferation, Wang et al designed a programmed delivery multifunctional hydrogel loaded with silver nanoparticles and rhCol III, and explored its effect on wound repair of chronic infection. The results of in vitro and in vivo showed that the silver ions released rapidly in the early stage can effectively remove bacteria and the sustained release of rhCol III in the later stage could effectively promote the migration of endothelial cells and the reconstruction of new blood vessels, thereby accelerating the repair of chronically infected wounds in diabetes 123–125 …”
Section: Smart‐responsive Hydrogels Employed For Different Tissue Rep...mentioning
confidence: 99%
“…The results of in vitro and in vivo showed that the silver ions released rapidly in the early stage can effectively remove bacteria and the sustained release of rhCol III in the later stage could effectively promote the migration of endothelial cells and the reconstruction of new blood vessels, thereby accelerating the repair of chronically infected wounds in diabetes. [123][124][125] 4.2 | Application of smart-responsive hydrogels in the repair of damaged myocardial tissue…”
Section: Application Of Smart-responsive Hydrogels In Chronic Wound T...mentioning
confidence: 99%